Morphology of stellar populations in the Magellanic Clouds using the VMC survey. Issue Volume 14:Issue S344(2019) (August 2018) - Youssoufi, Dalal El; Cioni, Maria-Rosa L.; Bell, Cameron P. M.; Rubele, Stefano; Niederhofer, Florian; Matijevic, Gal
Abstract: The Magellanic Clouds are nearby dwarf irregular galaxies that represent a unique laboratory for studying galaxy interactions. Their morphology and dynamics have been heavily influenced by their mutual interactions as well as with their interaction(s) with the Milky Way. We use the VISTA near-infrared YJK s survey of the Magellanic Clouds system (VMC) in combination with stellar partial models of the Large Magellanic Cloud (LMC), the Small Magellanic Cloud (SMC) and the Milky Way to investigate the spatial distribution of stellar populations of different ages across the Magellanic Clouds. In this contribution, we present the results of these studies that allow us to trace substructures possibly related to the interaction history of the Magellanic Clouds.